Shifting the Use of Karo Language to Indonesian for the Karo Community in Tanjung Sari Village, Medan Selayang District, Medan City: Sociolinguistic Study - Simbolon, Lustina; Sembiring, Sugihana Br; Ritonga, Parlaungan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to describe the process of language shift and the driving factors for the shift in the use of the language. This study is a type of qualitative descriptive research. The data source for this study is in the form of excerpts from interviews with 10 informants. The data collection techniques used were observation and conversation (interview) with capture techniques, face-to-face conversation techniques and recording and note-taking techniques. The data were analyzed using a theory with a sociolinguistic approach. The results of this study indicate that there is a process of shifting the use of Karo language into Indonesian in the second generation of children of the Karo language speaking community in Tanjung Sari Village, Medan Selayang District, Medan City. Of the 10 informants, 2 people experienced a subordinate bilingual process (B1>B2), 3 people experienced equivalent bilingualism (B1=B2) and 5 people experienced subordinate bilingualism (B2>B1) and were driven by migration factors, economic and social factors as well as school and education factors.